The Influence of The Role of Teachers In Preventing and Handling Bullying Cases In Elementary Schools - Olfah, Maria; Rahayu, Isnaniah; Theresia, Natali; Fahrizal, Muhammad Rizki; Rahmah, Jamilatur; Putri, Rahmah Eka; Elisa, Herni Nor; Hidayat, Ari (TROPICAL WETLAND JOURNAL, 2025)
This research aims to examine how teachers can influence the prevention and handling bullying cases at SDN SN Surgi Mufti 1, using various approaches, both product-based and non-product-based, as initial strategies to educate students about how negative impact of bullying. Bullying is defined as aggressive behaviour that is repeatedly carried out by an individual or a group towards another individual perceived as weaker, either physically or psychologically. This study employs a descriptive qualitative approach with a case study method conducted in a school located in a residential area, often attended by students from diverse backgrounds. Data were collected through observations and interviews with the school principal and teachers. The findings indicate that bullying, both physical and verbal, still frequently occurs in this school. Therefore, the schools has made various efforts to prevent bullying. These efforts include not only the use of product-based approaches but also non-product-based strategies to reduce bullying cases in the school.